The degree to which kindergarten teachers in Bani Obeid District possess distance learning skills and its relationship to some variables - Almomani, Hana Ali (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to identify the degree to which kindergarten teachers in Bani Obeid District possess distance learning skills and its relationship to some variables. Randomness from the study population, and after verifying the validity and stability of the tool, the study reached the most important results: There is a medium degree in the possession of kindergarten teachers in the Bani Obaid district of distance learning skills in the areas of (preparation and design of content in distance education, and in the field of teachers’ attitudes Kindergartens in the Bani Obaid District for distance learning skills As for the field of providing lessons in distance education, and evaluating students in distance education, it came to a medium degree, and this study showed that there were no statistically significant differences at the significance level (α≤0.05) in The degree to which kindergarten teachers in Bani Obeid District possess distance learning skills according to the variables (scientific qualification, type of education, number of years of experience, type of school) and based on the results of the study, the researcher recommended the necessity of teacher development, especially Kindergarten teachers in all technological and technical skills and various teaching skills, and the need to provide infrastructure in schools and for parents and laptops, including laptops and smart phones, to bridge the gap between the availability of information and the possibility of obtaining it due to the lack of a means of communication.